Pembaharuan Hukum Acara Peradilan Agama Telaah Eksistensi Pilihan Hukum, Pasal 50 dan Pasal 86 ayat (2) UU No.7 Tahun 1989 - Abdul Jamil (Jurnal Hukum IUS QUIA IUSTUM, 2002)
Law procedure at the religious court have tremendous progress recently and it has the exact law resource because the prevailing of Acts number 1 in the years of 1989, religious judicature have a unification on law of procedure. But in their implemeiitation the Acts number 7 in the year of 1989 has several law handicaps such as procedure case and law choice which are written on, the Acts of Religious Judicature that tends to impede the existence of Religious Judicature it self, The completing for the Acts number 7in the year of 1989 therefore deal with the common descnption point 2, paragraph 6 to confirm the existence of Religious Judicature which is suitable with the certainty of paragraph 2 and 49 the Acts nunfiber 1in the year of.1989 where they are very cruciai This writing Is going to discuss the problem of religious procedure law reform and the choice oflaw on inheritance.